A four-layer aluminum alloy plate with a corrosion potential gradient layered distribution and its preparation method and application

By introducing the corrosion potential gradient layered distribution of Zn and Mg into the aluminum alloy sheet, the strength and corrosion resistance problems caused by Si diffusion during the brazing process of the three-layer composite aluminum sheet are solved, and the high strength and excellent corrosion resistance of the four-layer aluminum alloy sheet are achieved.

CN120116553BActive Publication Date: 2025-08-26JIANGSU ALCHA ALUMINUM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510616914.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-08-26
Estimated Expiration
2045-05-14

AI Technical Summary

Technical Problem

During the brazing process, the existing three-layer composite aluminum plates have problems such as reduced strength, poor corrosion resistance, reduced tissue uniformity after welding and damaged corrosion performance due to Si diffusion, which is difficult to meet the requirements of large-scale engineering machinery engine plate-fin radiators.

Method used

A four-layer aluminum alloy sheet structure with a layered distribution of corrosion potential gradient is adopted, including the first cortex, an intermediate layer, a core layer and a second cortex. The intermediate layer contains Zn and the core layer contains Mg and Si. It is prepared by hot rolling, cold rolling and annealing processes. After brazing, a potential gradient is formed to prevent the diffusion of Si and Cu and optimize the corrosion mode.

Benefits of technology

The yield strength and tensile strength of aluminum alloy sheet after brazing are significantly improved, while the corrosion resistance is improved, the protection effect of potential gradient design is enhanced, and the overall performance of composite sheets is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120116553B_ABST
    Figure CN120116553B_ABST
Patent Text Reader

Abstract

The present invention discloses a four-layer aluminum alloy plate with a layered distribution of corrosion potential gradient, comprising a first skin layer, an intermediate layer, a core layer, and a second skin layer stacked in sequence, wherein the first skin layer and the second skin layer are 4-series aluminum alloys; the alloy composition of the intermediate layer comprises the following components by weight: Si: 0.5-1, Fe: 0.2-0.5, Cu: 0.05-0.1, Mn: 1.2-2, Zn: 2-3, Ti: ≤0.5, with the balance being aluminum; the alloy composition of the core layer comprises the following components by weight: Si: 0.5-1, Fe: 0.2-0.5, Cu: 0.2-0.5, Mn: 0.2-1, Mg: 0.1-0.3, Zn: ≤0.05, Ti: ≤0.5, with the balance being aluminum. The present invention also discloses a preparation method thereof, comprising stacking alloy blocks, followed by hot rolling, intermediate annealing, cold rolling, and final annealing, and discloses its application in vacuum brazing at 580-620°C. The four-layer aluminum alloy plate of the present invention improves mechanical properties while taking into account corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a multi-layer aluminum alloy plate and a preparation method and application thereof, belonging to the technical field of layered alloy preparation. Background Art

[0002] Composite aluminum sheeting is the primary material for heat exchangers. It's typically composed of three layers of aluminum alloy, consisting of a core layer and two skin layers. The core layer is typically an AA3xxx alloy (a wrought aluminum alloy based on the Al-Mn family), while the skin layers are AA4xxx alloys (near-eutectic Al-Si alloys). During brazing, the low-melting-point skin layer melts and wets the adjacent core layer. After cooling, the molten skin layer solidifies, forming a joint. However, due to the intense liquid-solid interaction during the brazing process, traditional three-layer composite aluminum sheet brazing methods struggle to achieve high-quality joints. In particular, they fail to meet the balanced strength and corrosion resistance requirements of plate-fin radiators used in today's large-scale engineering machinery engines. Key challenges include: 1. During brazing, silicon from the skin layer diffuses into the core metal, causing excessive dissolution of the core layer, reducing the strength and heat transfer performance of the aluminum heat exchanger and significantly negatively impacting its corrosion and fatigue resistance. 2. The skin layer fails to effectively protect the core layer, allowing corrosion to rapidly penetrate along grain boundaries into the core layer, ultimately leading to tube perforation and failure. Third, the solid-liquid interaction during the brazing process causes dissolution, corrosion, isothermal solidification, and liquid film migration, reducing the high-temperature load-bearing capacity of the composite aluminum plate and leading to overall collapse. Fourth, the liquid-solid interaction during the brazing process reduces the uniformity of the post-weld microstructure distribution, destroying the potential gradient design of the composite plate and seriously damaging the corrosion resistance of the composite plate.

[0003] The use of an anti-corrosion layer can improve the post-weld corrosion resistance of composite materials to a certain extent. For example, the prior art proposes to use AA7072 aluminum alloy with a lower corrosion potential as the anti-corrosion layer skin layer, and to protect the AA3003Mod core layer alloy as the cathode by sacrificial anode method, thereby improving corrosion resistance. However, this method uses a seventh-series aluminum alloy, which has high processing requirements and is also costly. There is also a prior art that proposes adjusting the ratio of the skin layer to the core layer to reduce the problem of melting corrosion and deterioration of corrosion resistance caused by the interaction between Al-Si alloy and Al-Mn alloy during high-temperature brazing of composite brazing aluminum materials. However, this method can only improve corrosion resistance, and cannot simultaneously improve post-weld mechanical properties. Summary of the Invention

[0004] To address the aforementioned shortcomings of the prior art, the present invention aims to provide a four-layer aluminum alloy sheet with a layered distribution of corrosion potential gradients. This aims to avoid the harmful effects of liquid-solid interactions such as liquid film migration, thereby producing a multi-layer composite aluminum sheet with excellent mechanical properties and corrosion resistance. Another objective of the present invention is to provide a method for preparing and applying a four-layer aluminum alloy sheet with a layered distribution of corrosion potential gradients.

[0005] The technical solution of the present invention is: a four-layer aluminum alloy plate with a corrosion potential gradient layer distribution, comprising a first skin layer, an intermediate layer, a core layer and a second skin layer stacked in sequence, wherein the first skin layer and the second skin layer are 4 series aluminum alloy;

[0006] The alloy composition of the intermediate layer includes the following components in weight percentage: Si: 0.5-1, Fe: 0.2-0.5, Cu: 0.05-0.1, Mn: 1.2-2, Zn: 2-3, Ti: ≤0.5, and the balance is aluminum;

[0007] The alloy composition of the core layer includes the following components in weight percentage: Si: 0.5-1, Fe: 0.2-0.5, Cu: 0.2-0.5, Mn: 0.2-1, Mg: 0.1-0.3, Zn: ≤0.05, Ti: ≤0.5, and the balance is aluminum.

[0008] Furthermore, the alloy composition of the intermediate layer includes the following components in weight percentage: Si: 0.8-0.9, Fe: 0.2-0.5, Cu: 0.05-0.1, Mn: 1.2-2, Zn: 2-3, Ti: ≤0.5, and the balance is aluminum;

[0009] The alloy composition of the core layer includes the following components in weight percentage: Si: 0.7-0.8, Fe: 0.2-0.5, Cu: 0.2-0.5, Mn: 0.2-1, Mg: 0.1-0.3, Zn: ≤0.05, Ti: ≤0.5, and the balance is aluminum.

[0010] Furthermore, the alloy composition of the intermediate layer includes the following components in weight percentage: Si: 0.8-0.9, Fe: 0.2-0.5, Cu: 0.05-0.1, Mn: 1.2-2, Zn: 2.5-2.6, Ti: ≤0.5, and the balance is aluminum.

[0011] Furthermore, the alloy composition of the core layer includes the following components in weight percentage: Si: 0.7-0.8, Fe: 0.2-0.5, Cu: 0.2-0.5, Mn: 0.2-1, Mg: 0.18-0.25, Zn: ≤0.05, Ti: ≤0.5, and the balance is aluminum.

[0012] Furthermore, the yield strength of the four-layer aluminum alloy plate after natural aging for 21 days after brazing is 80-91 MPa, and the tensile strength is 200-218 MPa.

[0013] Another technical solution of the present invention is: a method for preparing a four-layer aluminum alloy plate with a corrosion potential gradient layer distribution, comprising the following steps:

[0014] According to the alloy composition of the intermediate layer and the alloy composition of the core layer, the intermediate layer alloy block and the core layer alloy block are respectively cast;

[0015] From top to bottom, the 4 series aluminum alloy block, the middle layer alloy block, the core layer alloy block, and the 4 series aluminum alloy block are stacked and assembled to obtain an assembly;

[0016] The assembly is hot rolled, then intermediate annealed, and then cold rolled to the finished thickness, followed by a final anneal.

[0017] Furthermore, the thickness of the hot-rolled slab is 2.0 to 3 mm, and the thickness of the finished product is 0.20 to 0.25 mm.

[0018] Furthermore, the composite reduction rate of the hot rolling is 90% to 95%.

[0019] Furthermore, the intermediate annealing is to heat the hot-rolled slab to 450-480° C. at a heating rate of 30-40° C., keep the temperature for 10-15 hours and then air-cool.

[0020] Furthermore, the finished product annealing is to heat the finished product to 420-450° C. at a heating rate of 30-40° C., keep the temperature for 12-17 hours and then air-cool.

[0021] Furthermore, after the intermediate layer alloy block and the core layer alloy block are melt-casted, the intermediate layer alloy block and the core layer alloy block are heated to 280-500° C. at a heating rate of 30-50° C. / h for homogenization treatment.

[0022] Another technical solution of the present invention is: an application of a four-layer aluminum alloy plate with a corrosion potential gradient layered distribution, wherein the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution is vacuum brazed at a brazing temperature of 580-620°C.

[0023] The advantages of the present invention compared with the prior art are:

[0024] The four-layer aluminum alloy plate of the present invention adds a zinc-containing intermediate layer. On the one hand, it can prevent Si from penetrating from the skin layer to the core layer alloy, avoiding the preferential dissolution of the Al matrix around the Si particles caused by the micro-galvanic pairs between the Al matrix and the Si particles at the grain boundaries, thereby avoiding the generation of intergranular corrosion (IGC); on the other hand, it prevents the diffusion of Cu in the core layer into the skin layer, overcoming the phenomenon of accelerated corrosion of the Al matrix due to the diffusion of Cu into the skin layer to form Al2Cu.

[0025] During the brazing process of the four-layer aluminum alloy plate of the present invention, Zn in the Zn-containing Al-Mn alloy intermediate layer diffuses into the core layer, optimizing the potential gradient from the zinc-containing intermediate layer to the core layer, thereby changing the corrosion mode from pitting corrosion and intergranular corrosion (IGC) to exfoliation corrosion.

[0026] The core Al-Mn alloy of the four-layer aluminum alloy sheet of the present invention contains additions of Mg and Si, with the weight ratio of Mg to Si controlled within a range of 0.1 to 0.6. If the weight ratio is less than 0.1, the formation of the GP zone phase in the alloy is restricted, resulting in insufficient GP zone precipitation and a less pronounced strengthening effect. Especially at low Si contents, while Mg can form a solid solution, the precipitated phase may be larger in size, resulting in less than expected strengthening. If the weight ratio is higher than 0.6, excessive Mg precipitates, preventing it from forming a complex compound with Si (such as MgSi, Al2MgSi, and Al6MgSi). Excessive Mg may also reduce the alloy's plasticity and toughness, affecting its overall performance. Therefore, a Mg to Si weight ratio of 0.1 to 0.6 facilitates the precipitation of Mg and Si during natural aging after brazing, forming GP zones and producing a significant aging strengthening effect. After 21 days of natural aging, the aging strengthening effect reached its peak, with the yield strength of the brazed four-layer composite aluminum sheet increasing by approximately 50% and the tensile strength by approximately 25%. Furthermore, first-principles calculations showed that corrosion between the GP zone and the Al matrix was minimized, thereby improving mechanical properties while also maintaining the corrosion resistance of the aluminum sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the metallographic structure diagram of the cross section of the four-layer aluminum alloy plate with a layered distribution of corrosion potential gradient before and after brazing in Example 1.

[0028] Figure 2 Graph showing the microstructure and element distribution of the cross section of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution before and after brazing in Example 1.

[0029] Figure 3 This is a tensile stress-strain curve diagram of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution in Example 1 before and after brazing and after natural aging for different times.

[0030] Figure 4 These are glow discharge emission spectra of a conventional three-layer aluminum alloy plate and a four-layer aluminum alloy plate with a corrosion potential gradient layered distribution according to Example 1.

[0031] Figure 5 This is a TEM morphology of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution in Example 1 after brazing and natural aging for 21 days.

[0032] Figure 6 This is a corrosion voltage-current diagram of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution at different thicknesses in Example 1.

[0033] Figure 7This is a diagram showing the corrosion potential variation in the thickness direction of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution in Example 1.

[0034] Figure 8 These are the corrosion morphologies of a conventional three-layer aluminum alloy plate and a four-layer aluminum alloy plate with a layered distribution of corrosion potential gradient according to Example 1 at different stages of SWAAT.

[0035] Figure 9 The corrosion morphology at a depth of 80 μm of a traditional three-layer aluminum alloy plate and a four-layer aluminum alloy plate with a corrosion potential gradient layered distribution according to Example 1 after being placed in a SWAAT cabinet for 10 days.

[0036] Figure 10 This is the first-principles calculation model diagram of MgSi, Al2MgSi, and Al6MgSi compounds in the GP region. DETAILED DESCRIPTION

[0037] The present invention will be further described below with reference to the examples, but are not intended to limit the present invention.

[0038] The four-layer aluminum alloy plate with a corrosion potential gradient layered distribution of the present invention comprises four layers of alloy materials from top to bottom, namely a first skin layer, a middle layer, a core layer and a second skin layer.

[0039] The first skin layer and the second skin layer are 4 series aluminum alloys. In some specific embodiments, the first skin layer and the second skin layer can be selected from but not limited to AA4043, AA4343, AA4045, and AA4047 aluminum alloys.

[0040] The alloy composition of the intermediate layer includes the following components by weight: Si: 0.5-1, Fe: 0.2-0.5, Cu: 0.05-0.1, Mn: 1.2-2, Zn: 2-3, Ti: ≤0.5, and the balance is aluminum. The weight percentage of Zn can be, but is not limited to, 2.0, 2.1, 2.12, 2.18, 2.22, 2.3, 2.4, 2.48, 2.53, 2.6, 2.69, 2.7, 2.75, 2.78, 2.8, 2.9, or 3.0. The weight percentage of Si can be, but is not limited to, 0.5, 0.52, 0.55, 0.62, 0.70, 0.78, 0.85, 0.9, 0.96, or 1.

[0041] The alloy composition of the core layer includes the following components in weight percentage: Si: 0.5-1, Fe: 0.2-0.5, Cu: 0.2-0.5, Mn: 0.2-1, Mg: 0.1-0.3, Zn: ≤0.05, Ti: ≤0.5, and the balance is aluminum. The weight percentage of Mg can be, but is not limited to, 0.2, 0.25, 0.3, 0.35, 0.38, 0.4, 0.45, 0.5, 0.6, 0.68, 0.75, 0.85, 0.92, or 1. The weight percentage of Si can be, but is not limited to, 0.5, 0.52, 0.55, 0.62, 0.70, 0.78, 0.85, 0.9, 0.96, or 1.

[0042] The preparation method of the above-mentioned four-layer aluminum alloy plate with a layered distribution of corrosion potential gradient is as follows:

[0043] According to the alloy composition of the intermediate layer and the alloy composition of the core layer, the intermediate layer alloy block and the core layer alloy block are respectively cast.

[0044] The cast intermediate layer alloy block and the core layer alloy block can be heated to 280-500°C at a heating rate of 30-50°C / h for homogenization. The heating rate can be, but is not limited to, 30°C / h, 35°C / h, 40°C / h, 45°C / h, or 50°C / h, and the heating temperature can be, but is not limited to, 300°C, 320°C, 360°C, 420°C, or 500°C.

[0045] From top to bottom, the 4 series aluminum alloy block, the middle layer alloy block, the core layer alloy block, and the 4 series aluminum alloy block are stacked and assembled to obtain an assembly;

[0046] The assembled parts are hot rolled with a starting rolling temperature of 500°C and a final rolling temperature of 350°C to obtain 2.0-3 mm thick hot-rolled slabs. The thickness of the hot-rolled slabs can be, but not limited to, 2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm or 3 mm. The hot rolling composite reduction rate is 90% to 95%, specifically, it can be, but not limited to, 90%, 91%, 92%, 93%, 94% or 95%.

[0047] The thick hot-rolled slab is subjected to intermediate annealing, specifically heating to 450-480°C at a heating rate of 30-40°C, holding for 10-15 hours, and then air-cooling. It is then cold-rolled to a finished thickness of 0.20-0.3mm. The finished thickness can be, but is not limited to, 0.2mm, 0.22mm, 0.25mm, 0.26mm, 0.28mm, or 0.3mm.

[0048] Finally, the finished product is annealed, that is, the temperature is raised to 420-450°C at a heating rate of 30-40°C, maintained for 12-17 hours, and then air-cooled.

[0049] The application of the above-mentioned four-layer aluminum alloy plate with a corrosion potential gradient layered distribution is to vacuum braze the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution at 580-620°C. The brazing temperature can be, but is not limited to, 580°C, 590°C, 600°C, 610°C or 620°C. After brazing, it is naturally aged for 21 days. The yield strength is 80-91 MPa, which is 40%-50% higher than that of the unaged aluminum plate, and the tensile strength is 200-218 MPa, which is 20%-25% higher than that of the unaged aluminum plate.

[0050] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions. If the manufacturers of the reagents or instruments are not specified, they are all commercially available conventional products.

[0051] Example 1

[0052] This four-layer aluminum alloy sheet, with a layered corrosion potential gradient, consists of a first skin layer of AA4343 alloy, an intermediate layer, a core layer, and a second skin layer of AA4343 alloy. The intermediate layer's alloy composition by weight is: Si: 0.85, Fe: 0.26, Cu: 0.08, Mn: 1.62, Zn: 2.53, Ti: 0.02, with the balance being aluminum. The core layer's alloy composition by weight is: Si: 0.72, Fe: 0.36, Cu: 0.38, Mn: 0.58, Mg: 0.21, Zn: 0.02, Ti: 0.15, with the balance being aluminum. The first skin layer is 14 μm thick, the intermediate layer is 32 μm thick, the core layer is 160 μm thick, and the second skin layer is 27 μm thick.

[0053] The preparation method of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution is as follows:

[0054] (1) The intermediate layer alloy and the core layer alloy are cast according to the weight percentage components. After casting, they are heated to 300°C at a heating rate of 30°C / h for homogenization. Then, from top to bottom, AA4343 alloy, intermediate layer, core layer, and AA4343 alloy are assembled in sequence;

[0055] (2) The above-mentioned assembled parts are hot rolled at a starting temperature of 500°C and a final rolling temperature of 350°C to obtain a 2.2 mm thick hot-rolled slab with a hot rolling composite reduction ratio of 95%;

[0056] (3) Intermediate annealing: heating to 450°C at a rate of 40°C, maintaining for 12 hours and then air cooling;

[0057] (4) cold rolling the slab to obtain a 0.23 mm thick cold-rolled slab;

[0058] (5) Annealing of finished product: heating to 420℃ at a heating rate of 40℃, maintaining for 14 hours and then air cooling.

[0059] The brazing method of this embodiment is as follows: evacuate the vacuum brazing furnace to 5×10 -4 After the sample was heated to 600°C at a rate of 40°C / min and held at that temperature for 10 minutes, it was cooled in the furnace and then removed. After 21 days of natural aging, the yield strength reached 91 MPa, a 50% increase, and the tensile strength reached 218 MPa, a 25% increase.

[0060] In this embodiment, during the brazing process of the Al-Mn alloy containing a Zn intermediate layer, Zn diffuses into the core layer. According to first-principles calculations, the potential of the GP zone is not much different from that of the Al matrix, forming a potential gradient, which significantly improves the corrosion resistance of the composite plate.

[0061] Figure 1 Figure 2 shows the microstructure of a four-layer aluminum alloy sheet with a layered corrosion potential gradient before and after brazing, with (a) before brazing and (b) after brazing. Before brazing, the skin layer consists of an Al matrix and Si particles, while the core layer is dominated by a large number of Fe / Mn-containing particles. Clear interfaces between the skin, middle layer, and core layer are clearly visible. After brazing, the Al-Si eutectic phase is enriched on the surface of the resolidified skin layer and at the grain boundaries, while a large number of Mn-containing intermetallic compounds precipitate in the middle layer.

[0062] Figure 2 The microstructure and element distribution patterns of a four-layer aluminum alloy sheet with a laminar distribution of corrosion potential gradients before and after brazing are shown in Figures (a) before brazing and (b) after brazing. As can be seen, before brazing, Si particles are uniformly distributed throughout the cortex, while Fe / Mn-containing particles are dispersed in the core layer. Zn is added to the interlayer. After brazing, Al-Si eutectics are enriched at grain boundaries and on the surface of the resolidified cortex, while a large amount of Mn-containing intermetallic compounds precipitate in the interlayer. Driven by the concentration gradient, Zn diffuses from the interlayer into the core and cortex.

[0063] Figure 3The tensile stress-strain curves of a four-layer aluminum alloy sheet with a layered corrosion potential gradient distribution are shown before brazing and after natural aging for different times. The figure shows that the tensile strength of the four-layer aluminum alloy sheet before brazing reaches 170 MPa. Due to the complete recrystallization annealing in the O state, the sheet exhibits excellent plasticity, with the stress-strain curve exhibiting a flat, uniform flow region and an elongation of 16.7%. Table 1 shows that the tensile strength of the four-layer aluminum alloy sheet increases slightly after brazing, reaching 175 MPa. After 7, 14, and 21 days of natural aging, the tensile strength increases significantly, reaching 204 MPa, 216 MPa, and 218 MPa, respectively. After 21 days of natural aging, the age-strengthening effect reaches its peak. The yield strength of the brazed four-layer aluminum alloy sheet increases dramatically from 59 MPa to 91 MPa, an increase of approximately 50%, and the tensile strength increases from 175 MPa to 218 MPa, an increase of approximately 25%. The test standard for yield strength and tensile strength is: GB / T 228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method".

[0064] Table 1 Mechanical properties of the four-layer composite aluminum plate after different natural aging times in Example 1

[0065]

[0066] Figure 4 The glow discharge optical emission spectra (GDOES) of the conventional three-layer aluminum alloy plate and the four-layer aluminum alloy plate of the present invention are shown in FIG. Figure 4 As can be seen in (a), before brazing of the traditional three-layer aluminum alloy plate, the Si content in the skin alloy is 8wt.%. The dotted line corresponds to the depth distribution of the element before brazing. The solid line corresponds to the depth distribution of the element after brazing. After brazing, Si diffuses from the skin to the core layer. Figure 4 As can be seen in (a), the Si concentration on the resolidified cortex surface increases significantly. In addition, there is a clear segregation of copper on the surface after brazing, indicating that Cu diffuses from the core layer to the resolidified cortex after brazing. The Cu concentration near the resolidified cortex surface reaches 1wt.%. Similarly, Figure 4 As shown in Figure (b), the Zn concentration in the middle layer of the four-layer aluminum alloy sheet of the present invention is 2.43 wt.%. After brazing, Zn diffuses from the middle layer into the cortex and core layers. The Zn content decreases with increasing depth, optimizing the potential gradient from the middle layer to the core layer. After brazing, the Cu mass fraction near the resolidified cortex surface is 0.25 wt.%. The presence of the middle layer prevents Cu diffusion from the core layer to the middle layer, preventing Cu diffusion from the resolidified cortex surface.

[0067] Figure 5This is the TEM morphology of the four-layer composite aluminum plate after brazing and natural aging for 21 days. As can be seen from the figure, after a long period of natural aging, a large number of needle-shaped precipitates have precipitated in the core layer ( Figure 5 (a) and (b) in the figure). By analyzing Figure 5 The (001) Al crystal zone axis diffraction pattern shown in (c) is used to identify the precipitated phase, and the needle-shaped precipitate is completely coherent with the Al matrix.

[0068] like Figure 6 、 Figure 7 The figure shows the corrosion potential variation through the thickness of a four-layer composite aluminum plate. The figure shows significant differences in corrosion potential between the resolidified skin, intermediate layer, and core layer. From the surface of the composite aluminum plate toward the core layer, the corrosion potential first decreases and then increases. The overall corrosion potential of the skin layer is -710 mV, which is essentially consistent with the corrosion potential of the skin layer of the three-layer composite aluminum plate and should be the corrosion potential of resolidified AA4343. As the skin layer is removed, the polishing depth increases, exposing the intermediate layer material. Its corrosion potential is measured to be -760 mV, while the corrosion potential of the core layer is -670 mV. Because the intermediate layer contains Zn, its corrosion potential is approximately -760 mV, lower than the corrosion potentials of the resolidified skin layer (-710 mV) and the core layer (-670 mV). Due to the potential difference between the intermediate layer and the core layer, when they are connected to form a corrosion couple, the core layer becomes the cathode. This potential gradient allows the intermediate layer to provide effective cathodic protection for the core layer.

[0069] Figure 8 To compare and analyze the corrosion morphology of the traditional three-layer composite aluminum plate and the four-layer composite aluminum plate of the present invention at different stages of SWAAT. After brazing, the traditional three-layer composite aluminum plate was exposed in the SWAAT test chamber for 5 days. From the cross section of the sample, it can be clearly seen that there are pitting pits on the surface of the re-solidified skin, and there are obvious intergranular corrosion characteristics, such as Figure 8 As shown in (a) in the middle. As the test time increases, the corrosion develops along the grain boundaries of the primary α (A1) to the core layer, and quickly expands along the grain boundaries of the core layer, showing obvious intergranular corrosion morphology characteristics, such as Figure 8 Finally, after 25 days of SWAAT corrosion test, the intergranular corrosion in the traditional three-layer composite aluminum plate has basically penetrated the entire plate, and the plate has completely failed, as shown in Figure 2. Figure 8 In the four-layer composite aluminum plate containing the intermediate layer of the present invention, the resolidified skin layer in the early stage of corrosion also shows obvious intergranular corrosion morphology, as shown in FIG. Figure 8 However, since the potential of the Zn-containing interlayer is much lower than that of the cortex, after the intergranular corrosion enters the interlayer, the Zn-containing interlayer acts as a sacrificial anode, making the residual cortex a cathode, and the corrosion rapidly develops laterally in the sacrificial layer, as shown in Figure 2. Figure 8As shown in (d), as the corrosion progresses, the middle layer is consumed, and then the cathode phases such as eutectic Si in the remaining skin are peeled off together, avoiding the formation of corrosion galvanic pairs between the eutectic Si and the core layer, thus protecting the core layer from intergranular corrosion. Figure 8 The experimental results show that the four-layer composite aluminum plate of the present invention has excellent corrosion resistance. After 25 days of SWAAT test, the core layer still has no obvious permeation corrosion.

[0070] Figure 9 The corrosion morphology at a depth of 80 μm after 10 days in the SWAAT cabinet is shown in Figure 2. Figure 9 As shown in (a), the core layer of the traditional three-layer composite aluminum plate has severe corrosion (IGC and pitting), and severe intergranular corrosion has occurred, with an intrusion depth of >80μm; Figure 9 As shown in (b), the four-layer composite aluminum plate of the present invention exhibits good corrosion resistance, and no obvious local corrosion morphology is found at the core layer.

[0071] based on Figure 10 The first-principles calculations of the MgSi, Al2MgSi, and Al6MgSi compound models in the GP region were performed, and the density functional theory (DFT) was used to calculate the voltaic potential of the GP region (MgSi, Al2MgSi, and Al6MgSi). The potential of the GP region relative to the Al matrix was theoretically evaluated, and the calculated cutoff was 350 eV.

[0072] The volt potential difference between the intermetallic compound and the Al matrix ( ) is obtained by the following formula:

[0073]

[0074] in is the work function of the matrix, is the work function of the intermetallic compound.

[0075] The work function is calculated as follows:

[0076]

[0077] in is the vacuum energy level, is the Fermi energy.

[0078] Table 2 Calculated work functions of (100), (110), and (111) surfaces of Al and GP region compounds in Example 1

[0079]

[0080] The calculated work function of Al ranges from 3.99 eV on the (100) surface to 4.08 eV on the (100) surface. The calculated work function of the GP region ranges from 3.81 eV on the (111) MgSi surface to 4.17 eV on the (100) MgSi surface. The calculated results have a narrow discreteness. In ambient air, the work functions of the GP region (100), (110), and (111) surfaces do not differ significantly from the work function of the Al substrate.

[0081] Example 2

[0082] This four-layer aluminum alloy sheet, with a layered corrosion potential gradient, consists of a first skin layer of AA4343 alloy, an intermediate layer, a core layer, and a second skin layer of AA4343 alloy. The intermediate layer's alloy composition by weight is as follows: Si: 0.52, Fe: 0.2, Cu: 0.05, Mn: 1.22, Zn: 2.1, Ti: 0.04, with the balance being aluminum. The core layer's alloy composition by weight is as follows: Si: 0.5, Fe: 0.2, Cu: 0.22, Mn: 0.28, Mg: 0.12, Zn: 0.04, Ti: 0.28, with the balance being aluminum. The first skin layer is 14 μm thick, the intermediate layer is 32 μm thick, the core layer is 160 μm thick, and the second skin layer is 27 μm thick.

[0083] Example 2 was prepared using the same method as Example 1. The resulting four-layer aluminum alloy sheet with a gradient corrosion potential distribution was brazed using the same method as Example 1. After 21 days of natural aging, the yield strength reached 87 MPa, a 45% increase, and the tensile strength reached 207 MPa, an 18% increase. After 25 days of SWAAT testing, no significant permeation corrosion was observed in the core layer.

[0084] Example 3

[0085] This four-layer aluminum alloy sheet, with a layered corrosion potential gradient, consists of a first skin layer of AA4343 alloy, an intermediate layer, a core layer, and a second skin layer of AA4343 alloy. The intermediate layer's alloy composition by weight is as follows: Si: 0.96, Fe: 0.46, Cu: 0.1, Mn: 1.9, Zn: 2.82, Ti: 0.048, with the balance being aluminum. The core layer's alloy composition by weight is as follows: Si: 0.98, Fe: 0.47, Cu: 0.48, Mn: 1, Mg: 0.3, Zn: 0.01, Ti: 0.3, with the balance being aluminum. The first skin layer is 14 μm thick, the intermediate layer is 32 μm thick, the core layer is 160 μm thick, and the second skin layer is 27 μm thick.

[0086] Example 3 was prepared using the same method as Example 1. Four layers of aluminum alloy sheet material with a gradient corrosion potential distribution were brazed using the same method as Example 1. After 21 days of natural aging, the yield strength reached 89 MPa, a 48% increase, and the tensile strength reached 212 MPa, a 21% increase. After 25 days of SWAAT testing, no significant permeation corrosion was observed in the core layer.

[0087] Example 4

[0088] This four-layer aluminum alloy sheet, with a layered corrosion potential gradient, consists of a first skin layer of AA4343 alloy, an intermediate layer, a core layer, and a second skin layer of AA4343 alloy. The intermediate layer's alloy composition by weight is as follows: Si: 0.78, Fe: 0.2, Cu: 0.05, Mn: 1.22, Zn: 2.48, Ti: 0.04, with the balance being aluminum. The core layer's alloy composition by weight is as follows: Si: 0.7, Fe: 0.2, Cu: 0.22, Mn: 0.28, Mg: 0.12, Zn: 0.04, Ti: 0.28, with the balance being aluminum. The first skin layer is 12 μm thick, the intermediate layer is 29 μm thick, the core layer is 140 μm thick, and the second skin layer is 23 μm thick.

[0089] The preparation method of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution is as follows:

[0090] (1) The intermediate layer alloy and the core layer alloy are cast according to the weight percentage components, and then heated to 400°C at a heating rate of 40°C / h for homogenization. Then, the AA4343 alloy, intermediate layer, core layer, and AA4343 alloy are assembled from top to bottom in this order;

[0091] (2) The above-mentioned assembled parts are hot rolled at a starting temperature of 500°C and a final rolling temperature of 350°C to obtain a 2.0 mm thick hot-rolled slab with a hot rolling composite reduction ratio of 95%;

[0092] (3) Intermediate annealing: heating to 480°C at a rate of 30°C, maintaining for 10 hours and then air cooling;

[0093] (4) cold rolling the slab to obtain a 0.2 mm thick cold-rolled slab;

[0094] (5) Annealing of finished product: heating to 450℃ at a heating rate of 30℃, maintaining for 12 hours and then air cooling.

[0095] The resulting four-layer aluminum alloy sheet with a corrosion potential gradient was brazed using the same method as in Example 1. After 21 days of natural aging, the yield strength reached 89 MPa, a 48% increase, and the tensile strength reached 215 MPa, a 23% increase. After 25 days of SWAAT testing, no significant permeation corrosion was observed in the core layer.

[0096] Example 5

[0097] This four-layer aluminum alloy sheet, with a layered corrosion potential gradient, consists of a first skin layer of AA4343 alloy, an intermediate layer, a core layer, and a second skin layer of AA4343 alloy. The intermediate layer's alloy composition by weight is: Si: 0.9, Fe: 0.46, Cu: 0.1, Mn: 1.9, Zn: 2.6, Ti: 0.048, with the balance being aluminum. The core layer's alloy composition by weight is: Si: 0.85, Fe: 0.47, Cu: 0.48, Mn: 1, Mg: 0.25, Zn: 0.01, Ti: 0.3, with the balance being aluminum. The thickness of the first skin layer is 15 μm, the intermediate layer is 35 μm, the core layer is 172 μm, and the second skin layer is 29 μm.

[0098] (1) The intermediate layer alloy and the core layer alloy are cast according to the weight percentage components, and then heated to 500°C at a heating rate of 50°C / h for homogenization. Then, the AA4343 alloy, intermediate layer, core layer, and AA4343 alloy are assembled from top to bottom in this order;

[0099] (2) The above-mentioned assembled parts are hot rolled at a starting temperature of 500°C and a final rolling temperature of 350°C to obtain a 2.4 mm thick hot-rolled slab with a hot rolling composite reduction ratio of 95%;

[0100] (3) Intermediate annealing: heating to 460°C at a rate of 35°C, maintaining for 15 hours and then air cooling;

[0101] (4) cold rolling the slab to obtain a 0.25 mm thick cold-rolled slab;

[0102] (5) Annealing of finished product: heating to 440℃ at a heating rate of 35℃, maintaining for 17 hours and then air cooling.

[0103] The resulting four-layer aluminum alloy sheet with a corrosion potential gradient was brazed using the same method as in Example 1. After 21 days of natural aging, the yield strength reached 90 MPa, a 50% increase, and the tensile strength reached 214 MPa, a 22% increase. After 25 days of SWAAT testing, no significant permeation corrosion was observed in the core layer.

Claims

1. A four-layer aluminum alloy plate with a corrosion potential gradient layer distribution, comprising a first skin layer, an intermediate layer, a core layer and a second skin layer stacked in sequence, characterized in that: The first skin layer and the second skin layer are 4 series aluminum alloy; The alloy composition of the intermediate layer includes the following components in weight percentage: Si: 0.8-0.9, Fe: 0.2-0.5, Cu: 0.05-0.1, Mn: 1.2-2, Zn: 2.5-2.6, Ti: ≤0.5, and the balance is aluminum; The alloy composition of the core layer includes the following components in weight percentage: Si: 0.7-0.8, Fe: 0.2-0.5, Cu: 0.2-0.5, Mn: 0.2-1, Mg: 0.18-0.25, Zn: ≤0.05, Ti: ≤0.5, the balance is aluminum, and the weight ratio of Mg to Si is 0.1-0.

6.

2. The four-layer aluminum alloy plate with a corrosion potential gradient layered distribution according to claim 1, characterized in that: The four-layer aluminum alloy plate has a yield strength of 80 to 91 MPa and a tensile strength of 200 to 218 MPa after natural aging for 21 days after brazing.

3. A method for preparing a four-layer aluminum alloy plate having a corrosion potential gradient layered distribution according to claim 1 or 2, characterized in that: The following steps are involved: According to the alloy composition of the intermediate layer and the alloy composition of the core layer, the intermediate layer alloy block and the core layer alloy block are respectively cast; From top to bottom, the 4 series aluminum alloy block, the middle layer alloy block, the core layer alloy block, and the 4 series aluminum alloy block are stacked and assembled to obtain an assembly; The assembly is hot rolled, then intermediate annealed, and then cold rolled to the finished thickness, followed by a final anneal.

4. The method for preparing a four-layer aluminum alloy plate having a layered distribution of corrosion potential gradient according to claim 3, characterized in that: The thickness of the hot-rolled slab is 2.0-3 mm, and the thickness of the finished product is 0.20-0.25 mm.

5. The method for preparing a four-layer aluminum alloy plate having a layered distribution of corrosion potential gradient according to claim 4, characterized in that: The composite reduction rate of the hot rolling is 90% to 95%.

6. The method for preparing a four-layer aluminum alloy plate having a layered distribution of corrosion potential gradient according to claim 3, characterized in that: The intermediate annealing is to heat the hot-rolled slab to 450-480° C. at a heating rate of 30-40° C., keep the temperature for 10-15 hours and then air-cool.

7. The method for preparing a four-layer aluminum alloy plate having a layered distribution of corrosion potential gradient according to claim 3, characterized in that: The finished product annealing is to heat the finished product to 420-450° C. at a heating rate of 30-40° C., keep the temperature for 12-17 hours and then air cool the finished product.

8. The method for preparing a four-layer aluminum alloy plate having a layered distribution of corrosion potential gradient according to any one of claims 3 to 6, characterized in that: After the intermediate layer alloy block and the core layer alloy block are melt-casted, the intermediate layer alloy block and the core layer alloy block are heated to 280-500° C. at a heating rate of 30-50° C. / h for homogenization treatment.

9. An application of the four-layer aluminum alloy plate with a corrosion potential gradient layered distribution as claimed in claim 1 or 2, characterized in that: Four layers of aluminum alloy plates with a corrosion potential gradient layer distribution were vacuum brazed at a brazing temperature of 580-620°C.

Citation Information

Patent Citations

  • Multi-layer brazing sheet

    CN103492174A

  • High-corrosion-resistant multi-layer composite aluminum alloy pipe and producing method thereof

    CN109797323A